Personnel management in developing countries of South Asia - Shestha, Mangal K
The complexities of government in developing countries have been growing everyday and the governments have had to undertake the task of economic and social development. It requires the restructure and modernization of the civil service to enable them to fulfull their responsibilities. The civil service have adopted personnel management programmes that take there development into consideration. The author discusses the programmes and practices which make up the wide range of personnel management from recruitment, selection and appointment, to training, performance appraisal, and the reward system
Keywords: South Asia; Developing Country; Civil Service; Personnel